Assay of the Antifibrinolytic Activity in Human Plasma by Means of the Lysis Time Method - Ygge, J; Berg, W; Korsan-Bengtsen, K (Thrombosis and Haemostasis, 1968)
A one-stage lysis time method to determine the total antifibrinolytic activity of human plasma is described. Purified fibrinogen, thrombin, plasminogen, and urokinase were used in the test system. The necessity of using a high plasminogen concentration compared with the urokinase concentration is pointed out. The concentration of the reagents has to be carefully standardized.A straight line will be obtained in a semi-logarithmic system when plasma dilutions are plotted against. The validity of this relation is investigated when the concentrations of plasminogen, fibrinogen, and urokinase are varied. It is also shown that this relation is valied when the antifibrinolytic activity is increased postoperatively and after delivery.The antifibrinolytic activity is expressed as a percentage of the activity of a standard plasma. The standard plasma does not change its antifibrinolytic activity during storage at —20° C for at least three months.The error of the method is about 2%.Finally, the present report includes an experiment, the result of which makes it probable that the main action of plasma tested in this one-stage lysis time system is an antiplasmin activity.